Religiusitas dan Pengaruh Faktor Demografi Terhadap Kepatuhan Dalam Berzakat - Ivalaili Ivalaili (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
Zakat is one of the essential instruments in increasing community welfare as well as enhancing economic growth. To optimize potential zakat in Indonesia, it needs the involvement of various related parties both government and zakat institution and participation of muzakki as well. Based on the previous study it is known that external and internal factors influencing people compliance to pay zakat, external factors could be arisen from the environment, organization/ zakat institution and the obligation, while internal factors could come from religious factors, such as faith, altruism, demographic factors and social awareness. Aim of this study is to examine the influence of religiosity, and demographic factors on zakat. The questionnaire was distributed to 300 muzakki in Kota Tangerang. The findings show that religiosity had significantly related to zakat compliance. Demographic factors in this case gender and educational background have no significant influence on zakat compliance but give a positive effect, while the level of income have both positive impacts and significantly influence on zakat compliance